Diurnal Changes in Water Quality in Batang Ai Reservoir and Its Implications for Aquaculture - Elisha, Munsu (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study was carried out in the months of November 2013 and March 2014 to assess the diurnal changes in water quality at Batang Ai Reservoir, Sarawak. Water quality parameters were recorded at one station only which is S 17 (SALCRA cage culture) at different depths (subsurface, 10 m and 20 m). For nutrients, the range for nitrite 0.003 to 0.013 mg/L and TKN 0.051 to 0.799 mg/L. The concentrations of nutrients in March 2014 were slightly different compared to November 2014 because the water level of the reservoir was lower in March 2014. The range for BOD5 was from 4.07 to 14.78 mg/L, COD 84.5 to 220.48 mg/L, TSS from 0.8 to 9.0 mg/L and TS from 0.01 to 1.31 gg/L. The range of DO is between 0.2 to 8.1 mg/L. DO value was lower at 20 m because of low of oxygen. DO level was higher during day time but lower during night time except the first sampling at 5.00 pm and 9.00 pm which was due to current flow of the water. At 1.00 pm, the pH and temperature was recorded the highest which corresponded to high DO level for both samplings. Turbidity was higher during 9.00 am compared to night because the fish were being fed at that time.